EVALUATION OF MEHLICH - 3 AS A MULTIPURPOSE EXTRACTANT OF PHOSPHORUS AND POTASSIUM USING BELL PEPPER (Capsicum annuum L.) IN SOME NIGERIAN SOILS (2016)
Use of single soil specific extractants to determine plant available phosphorus and exchangeable potassium for crops such as bell pepper, are costly, laborious and time wasting. Bell pepper, rich in antioxidants, requires phosphorus and potassium for high quality fruit yield. Mehlich-3 (M3), a multi-purpose extractant could extract phosphorus and potassium simultaneously. However, M3 has not been evaluated and adapted for Nigerian soils. Therefore, M3 as a multi-purpose extractant of P and K from soil for bell pepper was evaluated. Phosphorus and potassium extractions were carried out on soil (0–15 cm) samples from 12 purposively selected sites belonging to eight soil series across three agro-ecological zones (derived savanna, humid forest and northern guinea savanna) of Nigeria. Bray 1 (B1), Bray 2 (B2) and Olsen were used to extract phosphorus; 1M Ammonium acetate pH 7.0 (AAc) was used to extract potassium, while M3, Ammonium hydrogen flouride+DTPA (ABD) and modified M3 (MM3) were used to extract phosphorus and potassium simultaneously. Concentrations of phosphorus and potassium extracted by different extractants were determined using standard procedures. In the screenhouse, pots were filled with 3 kg each of the 12 soil samples and laid in a completely randomised design (n=108). Bell pepper was grown at one plant per pot for four weeks. Phosphorus and potassium uptakes were determined. Field experiment was conducted on Egbeda, Apomu and Jago soil series for three cropping seasons to determine critical range of soil phosphorus and potassium and optimum fertiliser rates using M3. Phosphorus (0, 30, 45 and 60 kg/ha) and potassium (0, 15, 30 and 45 kg/ha) were applied in a split plot arrangement in a randomised complete block design, replicated thrice. Fruit yield of bell pepper was measured. Data were analysed using descriptive statistics, correlation and quadratic regression at α0.05. Phosphorus extracted by B1, B2, Olsen, ABD, MM3 and M3 were 8.34±1.22, 11.19±2.62, 5.11±1.68, 30.33±4.32, 15.68±3.48 and 14.41±4.32 mg/kg, respectively, while potassium extracted by AAc, ABD, MM3 and M3 were 0.47±0.02, 0.21±0.02, 0.36±0.05 and 0.59±0.09 cmol/kg, respectively. Phosphorus and potassium uptakes were 2.34±0.5 and 22.62±2.28 g/kg, respectively. Significant correlations exist between extracted phosphorus and potassium with their uptakes, except ABD for potassium. Correlations of phosphorus and potassium extracted by M3 with their uptakes were the highest (r=0.95), while the lowest was in B1 (0.78) for phosphorus UNIVERSITY OF IBADAN LIBRARY iii and MM3 (0.93) for potassium. The yields (t/ha) of bell pepper across seasons were 15.02±0.51 (Egbeda), 14.19±0.36 (Apomu) and 5.15±0.40 (Jago). Fruit yield was significantly influenced by applied fertilisers with phosphorus lowest in Apomu (r2=0.65) and highest in Jago (r2=0.99), for potassium, the least was in Jago (r2=0.52) and highest in Egbeda (r2=0.99). Critical ranges of phosphorus and potassium in the soils were 15 (Apomu) to 20 (Jago) mg/kg and 0.20 (Apomu) to 0.25 (Jago) cmol/kg, respectively. Optimum phosphorus and potassium concentrations for bell pepper were 45 kg/ha and 30 kg/ha, respectively. Mehlich-3 is a good simultaneous extractant of phosphorus and potassium across the agro-ecological zones. It is therefore recommended for evaluating soil phosphorus and potassium. Keywords: Multipurpose soil extractants; Mehlich-3 extractant; Phosphorus uptake; Bell pepper yield; Word count: 494